The Application of the Cooperative Model Type Student Teams Achievement Division (STAD) Assisted by Animated Video Learning Media on Narrative Text Writing Skills in Class X - Susilawati; Dindin; Meity Suratiningsih (Global Action and Education for Society, 2026)
This study aims to analyze the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model assisted by animated video media on narrative text writing skills of tenth-grade students at SMAN 17 Bandung. The research method employed a quasi-experimental design with nonequivalent control group, involving 72 students divided into experimental and control classes. Data collection was conducted through pretest, posttest, observation, and documentation, then analyzed using parametric statistics with SPSS 21.0. Results indicated significant improvement in the experimental class with average scores increasing from 1.67 to 2.5 (normalized gain 0.72), while the control class only improved from 1.55 to 1.93 (normalized gain 0.34). Paired sample t-test yielded significance value of 0.000 < 0.05, confirming meaningful differences between groups. The STAD model assisted by animated video proved effective in facilitating active collaboration and visual stimulation supporting writing creativity. Students demonstrated improvement in character development, characterization, and contemporary language style. This research recommends implementing this learning model as an innovative strategy to enhance narrative text writing skills at the senior high school level.